The mysterious Benedict Society and the prisoner's dilemma - Stewart, Trenton Lee.; Sudyka, Diana (London : The Chicken House, 2010)
Reynie, Kate, Sticky, and Constance investigate when an unexplained blackout engulfs Stonetown.
6.3
3-6.
3-6
Keywords: Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Adventure and adventurers -- Fiction; Friendship -- Fiction; Schools -- Fiction; Science fiction; Adventure fiction; Friendship -- Fiction; School stories; Science fiction; Adventure fiction; Science fiction